Iranian community-dwelling older adults' perceptions of prosociality: A qualitative study - Tahereh Ramezani; Nasibeh Zanjari; Hassan Rafiey; Ahmad Delbari (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: The world population is aging at an accelerating rate, and prosociality aspects increase in people with age. This study aimed to explore Iranian community-dwelling older adults' perspectives of the prosociality concept. MATERIALS AND METHODS: This qualitative study was conducted among older adults aged 60 years and older in Qom City, Iran. A purposive sampling method was used to collect data between July and October 2022. Semi-structured interviews were conducted with 25 older adults engaged in various types of prosocial activities. Data were analyzed applying a directed content analysis approach. All interviews were audio recorded, transcribed verbatim, and coded using MAXQDA 20 software. RESULTS: Overall, 5 main categories and 19 subcategories emerged from the content data analysis. The two emerged categories were related to the predetermined dimensions of the prosociality concept, namely, "prosocial behaviors" and "prosocial dispositions." The remaining three newly emerged categories included "egocentric motives," "facilitators," and "barriers" to prosocial behaviors. As participants reported, "informal spontaneous helping" was the most prevalent subcategory of prosocial behaviors. "Prosocial norms" and "social reward-seeking" were identified as the most common subcategories of prosocial dispositions and egocentric motives, respectively. Likewise, participants mentioned "religious and metaphysic beliefs" and "social distrust" as important facilitators and barriers, respectively. CONCLUSIONS: The results of this qualitative study provide a new understanding of the prosociality concept among older adults in the context of Iran. In conclusion, to improve prosocial behaviors in this population, the interaction between all factors that influence it such as motives, facilitators, and barriers must be considered.